Analytical study of the economic effects of sports for seniors in Iran - Lida Moazen Ahmadi; Hassan Fahim Devin; Zahrasadat Mirzazadeh; Hossein Peymanizad (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.